A rigid ringlike molecule: large second-order nonlinear optical performance, good temporal and thermal stability, and ideal spherical structure conforming to the "site isolation" principle. Issue 25 (19th June 2018) - Chen, Pengyu; Liu, Guangchao; Zhang, Huanyu; Jin, Meng; Han, Mengmeng; Cheng, Ziyao; Peng, Qian; Li, Qianqian; Li, Zhen
Abstract : Ringlike moleculeR1 containing two FTC moieties exhibited excellent EO performance ( d 33 = 562 pm V −1 @1950 nm, T 80% = 145 °C). Abstract : In this paper, according to the principle of site isolation, a ringlike molecule ofR1, based on the second-order nonlinear optical chromophore of FTC (Fang's Thermally-Stable Chromophore), was designed and synthesized, in which, the heads and waists of two FTC moieties were locked together through chemical bonds, respectively. Thanks to the ideal spherical structure and good alignment of the two pieces of FTC moieties, R1 exhibited an ultra high nonlinear optical effect with a d 33 value of 562 pm V −1 at a wavelength of 1950 nm, which could still retain 80% at a very high temperature of 145 °C.